Where you see yourself - Forrest, Claire (Young adult author) (Scholastic Press, 2023)
Effie Galanos' goals for her senior year include her navigating her way through her high school that is not really wheelchair-friendly, getting into the perfect college, and getting her crush Wilder to accompany her to the prom--but by spring she is beginning to see herself entirely differently.